Dual inhibition of Mcl-1 by the combination of carfilzomib and TG02 in multiple myeloma. Issue 7 (2nd July 2016) - Ponder, Katelyn G.; Matulis, Shannon M.; Hitosugi, Sadae; Gupta, Vikas A.; Sharp, Cathy; Burrows, Francis; Nooka, Ajay K.; Kaufman, Jonathan L.; Lonial, Sagar; Boise, Lawrence H.
ABSTRACT: Carfilzomib (Kyprolis®), a second generation proteasome inhibitor, is FDA approved for single-agent use among relapsed/refractory multiple myeloma (MM). To enhance the therapeutic efficacy of carfilzomib, we sought to combine carfilzomib with other novel agents. TG02, a multi-kinase inhibitor, targets JAK2 and CDK9. The rationale for co-treatment with carfilzomib and TG02 is that both independently target Mcl-1 and most myeloma cells are dependent on this anti-apoptotic protein for survival. We observed at least additive effects using the combination treatment in MM cell lines and patient samples. To determine how the bone marrow environment affects the efficacy of the combination we conducted co-culture experiments with Hs-5 stromal cells. We also examined the mechanism of increased apoptosis by determining the affect on expression of the Bcl-2 family of proteins. We found that carfilzomib increases NOXA mRNA expression, as expected, and TG02 treatment caused a decrease in Mcl-1 protein but not mRNA levels. Consistent with this possibility, we find silencing CDK9 does not change carfilzomib sensitivity in the same manner as addition of TG02. Since changes in Mcl-1 protein occur in the presence of a proteasome inhibitor we hypothesize that regulation of Mcl-1 translation is the most likely mechanism. Taken together our data suggest that dual inhibition of Mcl-1 via decreased expression and the induction of its antagonist NOXA by the combination of carfilzomib and TG02 is active in myeloma and warrants further testing preclinically and in clinical trials. Moreover, regulation of Mcl-1 by TG02 is more complex than initially appreciated.